Law Enforcement Against Perpetrators of the Crime of Smuggling Imported Used Clothes According to Positive Law - Haekal Abdatamma Ramadhan; Muchamad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2023)
Smuggling is an act that controls goods by stealth which certainly violates laws and regulations. Lately, the crime of smuggling imported used clothes often occurs in Indonesia. This is motivated by the Indonesian people who are more interested in foreign products and the price is sloping. So that these smuggling individuals are interested in taking greater advantage of this act of smuggling imported used clothes. On this occasion, the author uses a normative juridical method based on Indonesia's positive legal perspective. Then, this type of research uses qualitative descriptive with data analysis techniques derived from literature studies by reviewing books and involving literature related to the problems raised in this journal. Enforcement against the perpetrators of the crime of smuggling imported used clothes cannot be underestimated. The government together with law enforcement officials, especially customs, must be more responsive in monitoring the gaps in the entry of goods from abroad. Law enforcement against perpetrators must be dealt with firmly, considering that this smuggling has had a major impact on the country's income and progress. Various laws and regulations have long been present to maintain the smuggling attempt, only later the government and the government can carry out these regulations optimally.